2019
DOI: 10.1002/1878-0261.12560
|View full text |Cite
|
Sign up to set email alerts
|

A SOX9‐AS1/miR‐5590‐3p/SOX9 positive feedback loop drives tumor growth and metastasis in hepatocellular carcinoma through the Wnt/β‐catenin pathway

Abstract: Hepatocellular carcinoma (HCC) is a prevalent solid tumor with a high global death rate. SRY box 9 (SOX9) has been reported as an oncogene in HCC by several studies, but the underlying mechanism remains largely unexplored. Here, we confirmed upregulation of SOX9 in HCC tissues and cell lines and validated that SOX9 facilitates proliferation, migration and invasion in HCC. We subsequently identified that the long non‐coding RNA (lncRNA) SOX9 antisense RNA 1 (SOX9‐AS1) is a neighbor gene to SOX9; SOX9‐AS1 is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…For example, down-regulation of lncRNA ZEB1-AS1 suppresses the proliferation and invasion in OSCC by inhibiting ZEB1 [41]. LncRNA SOX9-AS1 positively regulates SOX9 in hepatocellular carcinoma and drives tumor growth [42]. Here, we examined the level of TMPO mRNA in cells transfected with TMPO-AS1-specific shRNAs and identified that TMPO-AS1 positively regulated TMPO in TC cells.…”
Section: Discussionmentioning
confidence: 98%
“…For example, down-regulation of lncRNA ZEB1-AS1 suppresses the proliferation and invasion in OSCC by inhibiting ZEB1 [41]. LncRNA SOX9-AS1 positively regulates SOX9 in hepatocellular carcinoma and drives tumor growth [42]. Here, we examined the level of TMPO mRNA in cells transfected with TMPO-AS1-specific shRNAs and identified that TMPO-AS1 positively regulated TMPO in TC cells.…”
Section: Discussionmentioning
confidence: 98%
“…Previous study demonstrated that lncRNA SNHG14 sponged miR-5590-3p to promote prostate cancer malignancy [34]. LncRNA SOX9-AS1 axis could play regulatory role in metastasis in hepatocellular carcinoma by targeting miR-5590-3p to regulate Wnt/β-catenin pathway [17]. SNHG14 and SOX9-AS1 in TNBC may also affect cell function by targeting miR-5590-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that miR-5590-3p is also involved in the regulation of cancer, being able to inhibit diffuse large B cell lymphoma progression and immune evasion [16]. In addition, it can also regulate tumour growth and metastasis in hepatocellular carcinoma through the Wnt/β-catenin pathway [17]. In particular, miR-5590-3p is downregulated in TNBC [18].…”
mentioning
confidence: 99%
“…Glycogen synthase kinase 3β (GSK3β) is a pivotal regulator of β-catenin signaling[ 102 ], and the lncRNA SNHG5 acts as a miR-26a-5p sponge to enhance GSK3β expression, thereby activating the Wnt/β-catenin pathway to facilitate HCC metastasis and EMT[ 103 ]. In addition, sex determining region Y-box (SOX) 9 can activate the Wnt/β-catenin pathway in HCC[ 104 ], and the lncRNA S OX9-AS1 facilitates HCC growth and metastasis by increasing SOX9 expression to activate the Wnt/β-catenin pathway by acting as a miR-5590-3p sponge[ 105 ]. In HCC, interleukin (IL)-6 is associated with the activation of Janus kinase 2 (JAK2)/STAT3 signaling[ 106 ]; cyclin-dependent kinase (CDK) 8 and low-density lipoprotein receptor-related protein 6 (LRP6) are associated with the activation of Wnt/β-catenin signaling[ 107 , 108 ], and the lncRNA DLGAP1-AS1 increases the expression of IL-6 and CDK8/LRP6 by functioning as a sponge of miR-26a-5p and miR-26b-5p, thereby activating JAK2/STAT3 and Wnt/β-catenin signaling to facilitate EMT and the progression of HCC, respectively[ 109 ].…”
Section: Role Of Lncrnas As Cernas In Hccmentioning
confidence: 99%